CONSTRUCTION OF THE MEANING OF NUJA ANNAFI WRITE BATIK IN NUSANTARA JAYA VILLAGE, KERITANG DISTRICT, INDRAGIRI HILIR DISTRICT: KONSTRUKSI MAKNA BATIK TULIS NUJA ANNAFI DI DESA NUSANTARA JAYA KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - TINA (Journal Of Social And Political Science, 2024)
Batik is a cultural product that has long been developed and known by the people of Indonesia. Batik is synonymous with process techniques, from depicting motifs to drooping. The construction of meaning is related to the way of communication, because in constructing meaning people carry out symbolic interaction methods in which interaction is established in society. This study uses a qualitative method. Data collection techniques in this study used interviews, observation and documentation. The subjects of this study were batik craftsmen and the people of Nusantara Jaya village. The technique of analyzing data on Nuja Annafi's Batik Meaning Construction uses the theory of Symbolic Interaction. This theory explains that meaning is formed through the process of communication. This communication process can be seen from the assumptions contained in the Symbolic Interaction theory, namely Mind, Self, and Society. The results of this study are that Nuja Annafi batik is interpreted as a cultural identity, Nuja Annafi batik is interpreted as an industrial work, Nuja Annafi batik is interpreted as an economic identity, Nuja Annafi batik is interpreted as a symbol of wealth, Nuja Annafi written batik is based on social strata. The construction of the meaning of the Nuja Annafi batik cloth was created because of a process of symbolic interaction felt by the people of Nuisantara Jaya village. This theory of symbolic interaction makes citizens master the values ​​and meanings contained in Nuja Annafi's batik cloth, namely striking colors such as yellow as a symbol of Malay culture meaning glory, majesty and purity. The Nuja Annafi batik motifs also have significant values ​​such as the Pucuk Rebung Putri motif which symbolizes a strength in upholding custom to educate an individual's morals. after that the community has a construction of meaning regarding the cloth they want implemented in works of art is batik. Keywords: Meaning Construction, Written Batik, Nuja Annafi